Pharmacognosic Study and Determination of Marker Compounds Soursop Leaves (Annona muricata) - M. Arifuddin; Faisal, Muhammad; Samsul, Erwin; Hikmawan, Baso Didik; Prabowo, Wisnu; Ahmad, Islamudin; Ibrahim, Arsyik (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2024)
Soursop (Annona muricata) is reported to have great efficacy in traditional medicine in Indonesia so it is very vulnerable to being faked or sold as low quality. Apart from having a delicious fruit taste, Soursop leaves have also been used as an effective cancer medicine by the public and have been scientifically proven so that Soursop can be used as a phytopharmaceutical product. Therefore, it is necessary to carry out research to determine pharmacognosy parameters and marker compounds as ingredients needed to obtain the authenticity of simplicia and plant extracts. This research includes macroscopic and microscopic examination of leaves, macroscopic and microscopic examination of simplicia, fluorescence characteristics of simplicia, determining the solubility of methanol extract in various non-polar and polar solvents as well as the characteristics of marker compounds that can be used as alternatives to existing marker compounds from Soursop (Annona muricata). The research results obtained are important information as a stage for the identification and standardization of soursop leaves (Annona muricata) as a raw material for herbal medicine.